High-Performance Distributed Objects over System Area Networks - Forin, Alessandro; Hunt, Galen; Li, Li; Wang, Yi-Min (Third USENIX Windows NT Symposium, 1999)
Describes an approach to build commercial high-performance distributed object systems over system area networks (SANs) with user-level networking. The specific platforms we use in this study are the Virtual Interface Architecture (VIA) and Microsoft's Distributed Component Object Model (DCOM). We give a detailed functional and performance analysis of DCOM and apply optimizations at several layers to take full advantage of modern high-speed networks. Our optimizations preserve the full set of DCOM features, including security, alternative threading models and the Microsoft Transaction Server (MTS). Through extensive runtime, transport and marshaling optimizations, our system achieves round-trip latencies of 72 mu s for DCOM calls and 174 mu s for MTS calls, and an application bandwidth of 86.1 MByte/s. We also examine the performance gains in real applications.